Information Literacy as a Da’wah Model in Combating Terrorism. - Muliyadi, Irvan (Jurnal Mercusuar, 2020)
The progress of information and communication technology has changed how information is recorded, stored, and accessed. Everyone has the opportunity to publish and access writings about jihad on the internet. Therefore, anyone can be exposed to radical and fundamentalist ideologies through reading about Jihad on the Internet or through direct calls to jihad by radical or fundamentalist groups. Information literacy, defined as a set of knowledge and skills related to information, is the foundation for reducing terrorist actions. This knowledge and skills include the ability to create information search strategies, access information, evaluate the reliability of information, understand information, disseminate information, and use information. The information literacy preaching model to combat terrorism includes conveying to the audience the following: strategies for searching for information on jihad on the internet by entering keywords such as jihad, synonyms of jihad, variants of jihad or related words to jihad, such as arhaba and its variants; evaluating the authority of the author by looking at their biography, evaluating the quality of the writing by looking at its references and possible biases; providing a foundation for understanding the verses about jihad, disseminating true information about jihad through various media, and using or applying the true meaning of jihad in their lives.